Identification of Cancer Stem Cell (CSC)-Associated Genes, Prognostic Value, and Candidate Drugs as Modulators of CSC-Associated Signaling in Carcinomas Through a Multiomics Data Analysis Approach - Pallabi Mondal; Poulami Singh; Krishna Mahanti; Sankar Bhattacharyya (Informatics)
Background: Cancer stem cells (CSCs) are a small subpopulation of cancer cells that have the potential for self-renewal and a strong proliferative capacity, and sustain tumorigenesis capabilities. This ability of CSCs to escape immune responses makes the CSCs a primary source of functionally altered, immune-resistant, chemoresistant, aggressive tumor cells. These characteristics determine the potential advantage of targeting CSCs for the treatment of solid tumors. Method: First, we downloaded different gene expression datasets of CSCs from the NCBI-GEO (National Center for Biotechnology Information–Gene Expression Omnibus) database and identified common genes by using a suitable Venn tool. Subsequently, we explored the prognostic significance of the particular genes in particular cancers and analyzed the expression of these genes at the protein level in human solid tumors by using KM plotter (Kaplan-Meier plotter) and an HPA (The Human Protein Atlas) database, respectively. Finally, using a comparative toxicogenomic database, we selected several important drugs or chemicals. Result: From this study, we identified APOC1 as a common upregulated gene in breast cancer and SLC44A5 and CAV2 as common up- and downregulated genes in lung cancer. In ovarian cancer, PRRG4 is a commonly upregulated gene, and ADCY7, AKAP12, TPM2, and FLNC are commonly downregulated genes. These genes also show prognostic significance in respective cancers. Several drugs that are capable of targeting the expression or signaling network of designated genes of CSC were also identified, which may contribute in CSC-targeted cancer therapy. Conclusion: Our study suggests a need for more in-depth experimental investigations to determine the actual functional activity and the mechanism of action of these CSC-associated genes.